The Strategy of Ideology Tracking on the Novel Bumi Manusia through a Mental Model - ., Rahutami (KnE Social Sciences, 2018)
The novel Bumi Manusia has become a phenomenon due to its ideological polemic. Ideology shows the basic beliefs that govern the attitude of the author and underlie the process of recounting the novel. The search is done by using a pragmatic approach that considers the novel as an utterance of purpose. The analysis was done by using a pragmatic method. Based on the results of the analysis it can be stated that the novel Earth Human criticizes the elements of society that are against humanism on the issues of education, race, gender, and law. A writer’s strategy can be traced through: (1) a person’s scheme, which describes the physical and mental aspects of the author, as well as comments from other figures as a description of the views contained in society; (2) self-schema that can be traced through the author’s response to various views of society; (3) role schemes as the author’s way of criticizing various views of community groups; and (4) event schemes involving actual events as backgrounds and things that the author criticizes. Based on this, the mental scheme indicates that the authors reinforce the theme of a resistance attitude to the conflict faced and arouse the spirit of unyielding struggle to fight for the values of humanity in his life. Keywords: ideology, mental model, strategy